Prospects for legalizing decentralized prediction markets in the US on the example of the Polymarket case - Tuholukov, Yaroslav (Здобутки економіки: перспективи та інновації, 2026)
The purpose of the study is to comprehensively assess the legal and economic prerequisites for integrating prediction markets into the US financial system, taking into account the regulation of derivative financial instruments, gambling legislation, and the characteristics of decentralized management models, as well as to determine the impact of legalization on the informational efficiency of markets and the stability of the financial system. The study uses formal legal analysis of regulatory acts and law enforcement practices of federal authorities, a comparative legal approach to the distinction between financial and gambling regulation, economic and mathematical modeling using autoregressive models with external variables and rational expectations theory, as well as elements of agent-based modeling to assess the risks of price manipulation. The source base consists of relevant scientific publications from 2022 to 2026, analytical materials, and regulatory documents. It has been established that the main barrier to integrating decentralized prediction markets into the US legal framework is the dual legal nature of event contracts, which creates competition between the regulatory regimes governing derivatives markets and the gambling sector. It has been proven that the absence of a centralized issuer in decentralized autonomous organizations complicates state supervision and the identification of the responsible entity. Economic analysis confirmed the ability of binary contracts to aggregate scattered information and form market expectations more efficiently than individual traditional indicators, while also revealing the risks of short-term price distortions. The need to introduce a mixed legal support model, combining distributed registries with a licensed organizational form of activity, is justified. Legalization of prediction markets, provided that there is a clear distinction between financial and gambling regulation, can increase the transparency of market expectations and expand the range of risk management tools without creating excessive systemic threats.